2015
DOI: 10.1002/cjce.22234
|View full text |Cite
|
Sign up to set email alerts
|

Performance of alkali‐free natural petroleum sulfonates: Ultra‐low interfacial tension on oil/water interface

Abstract: Ultra‐low interfacial tension (IFT) is one of the most important conditions relating to surfactant flooding for enhanced oil recovery. In this paper, the dynamic interfacial tension (DIT) of an alkali‐free petroleum sulfonate surfactant was studied with the spinning drop method aimed at the Daqing oil/water system. The effects of various experimental conditions, such as surfactant concentration, inorganic salt concentration, polar organic compounds, oil‐soluble sulfonates, and time stability were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[7][8][9][10][11] The adsorption of these components at the interface results in distinctive mechanical properties of the oil-water interface like ultra-low IFT 12 and viscoelasticity. 13 Among them, ions are commonly seen but have considerable effects on the interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] The adsorption of these components at the interface results in distinctive mechanical properties of the oil-water interface like ultra-low IFT 12 and viscoelasticity. 13 Among them, ions are commonly seen but have considerable effects on the interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Results are promising; a person shows promise; The results of the tests, study, or method are promising. We consider show in this case to be a feeble verb.[p. 109]Furthermore, the oils used for DIT measurements were simulated oil A spinning drop tensiometer measured the DIT of the simulated oils.[p. 1410]…”
Section: Vigorous Versus Feeble Verbsmentioning
confidence: 99%
“…16 The alkali-free petroleum sulfonate surfactant studied by Weng et al showed that the petroleum sulfonates with high molecular weight are able to reduce the IFT more effectively. 17 Surfactants with highly branched large hydrophobes are required to obtain the ultralow IFT for future applications. 18 In most cases, it is hard for an individual surfactant to achieve ultralow IFT but relatively easy for a surfactant mixture.…”
Section: Introductionmentioning
confidence: 99%